Experience with selective venous sampling in diagnosis of ACTH-dependent Cushing's syndrome. Issue 6308 (2nd January 1982) - Drury, P L; Ratter, S; Tomlin, S; Williams, J; Dacie, J E; Rees, L H; Besser, G M
Abstract : Twenty-three patients with adrenocorticotrophic hormone-(ACTH)-dependent Cushing's syndrome were subjected to selective venous catheterisation and sampling for ACTH on a total of 26 occasions. Out of 10 patients with pituitary-dependent disease, nine had raised ACTH concentrations in one or both high internal jugular vein samples. Eight patients had 11 proved sites of ectopic hormone production: of these, six were correctly identified by the sampling technique, and in four of them this was the only accurate method of localisation. The results of one catheterisation were misleading, and on 10 occasions they were inconclusive; five patients remained undiagnosed by any method. Overall, 15 of the 26 catheterisations provided diagnostically valuable information. Selective venous catheterisation and sampling for ACTH is effective in confirming a pituitary source of the hormone and may be valuable in locating the source of ectopic ACTH production in some cases.